Surveillance of Diarrheagenic Escherichia coli Strains Isolated from Diarrhea Cases from Children, Adults and Elderly at Northwest of Mexico - Canizalez-Roman, Adrian; Flores-Villaseñor, Héctor M.; Gonzalez-Nuñez, Edgar; Velazquez-Roman, Jorge; Vidal, Jorge E.; Muro-Amador, Secundino; Alapizco-Castro, Gerardo; Díaz-Quiñonez, J. Alberto; León-Sicairos, Nidia (Frontiers in Microbiology, 2016)
Diarrheagenic Escherichia coli (DEC) strains are a main cause of gastrointestinal disease in developing countries. In this study we report the epidemiologic surveillance in a four-year period (January 2011 to December 2014) of DEC strains causing acute diarrhea throughout the Sinaloa State, Mexico. DEC strains were isolated from outpatients of all ages with acute diarrhea (N=1,037). Specific DEC pathotypes were identified by PCR-amplification of genes encoding virulence factors. The adhesion phenotype and antibiotic resistance were also investigated. DEC strains were detected in 23.3% (242/1037) of cases. The most frequently DEC strain isolated was EAEC [(12.2%), 126/242] followed by EPEC [(5.1%), 53/242], ETEC [(4.3%), 43/242] DAEC [(1.4%), 15/242], STEC [(0.3%), 3/242] and EIEC [(0.2%), 2/242]. EHEC strains were not detected. Overall DEC strains were more prevalent in children ≤ 2 years of age with EPEC strains the most common of DEC pathotypes. While 65% of EAEC strains were classified as typical variant based on the aggregative adherence to in vitro cultures of HEp-2 cells, a high proportion of EPEC strains was classified as atypical strains. EAEC, EPEC, ETEC and DAEC strains were distributed in the north, central and south regions of Sinaloa state. Among all DEC strains, >90% were resistant to at least one commonly prescribed antibiotic. Strains were commonly resistant to first-line antibiotics such as tetracycline, ampicillin and sulfamethoxazole-trimethoprim. Furthermore, more than 80% of DEC isolates were multi-drug resistant and EPEC and DAEC were the categories with major proportion of this feature. In conclusion, in nearly one out of four cases of acute diarrhea in Northwestern Mexico a multi-drug resistant DEC strain was isolated, in these cases EAEC was the most prevalent (52%) pathotype.